Safety of Rimegepant in Adults with Migraine and Anxiety, Depression, or Using Antidepressants: Analysis of a Multicenter, Long-Term, Open-Label Study - David Kudrow; Susan Hutchinson; Glenn C. Pixton; Terence Fullerton (Pain and Therapy)
Abstract Introduction Anxiety and depression are frequently associated with migraine, and antidepressant use can complicate treatment. These analyses assessed the safety and tolerability of rimegepant in participants with migraine and anxiety and/or depression, or using selective serotonin reuptake inhibitors (SSRIs) and/or other antidepressants. Methods Data were from a phase II/III safety study of rimegepant for the acute treatment of migraine. Participants with a history of 2–14 migraine attacks per month of moderate or severe pain intensity self-administered rimegepant 75 mg as needed up to once daily for up to 52 weeks. These post hoc subgroup analyses assessed safety according to self-reported history of anxiety (yes or no) or depression (yes or no), and current use of SSRIs (yes or no) or other antidepressants (yes or no). Results Of 1800 treated participants, 23.2% (n = 417) had a self-reported history of anxiety, 23.7% (n = 426) had a self-reported history of depression, and 11.2% (n = 202) reported both anxiety and depression. A total of 10.1% (n = 181) of participants were using an SSRI, 10.8% (n = 195) were using other antidepressants, and 1.8% (n = 32) were using both. Across the subgroups with anxiety, without anxiety, with depression, without depression, using SSRIs, not using SSRIs, using other antidepressants, and not using other antidepressants, respectively, similar proportions of participants reported adverse events (67.1%, 58.4%, 62.0%, 60.0%, 64.1%, 60.0%, 66.2%, 59.8%), serious adverse events (3.6%, 2.3%, 2.8%, 2.5%, 3.3%, 2.5%, 5.1%, 2.3%), and discontinuation of rimegepant due to adverse events (4.1%, 2.2%, 3.1%, 2.5%, 5.0%, 2.4%, 3.1%, 2.6%). Numerical improvements in a variety of participant-reported outcomes were also observed at weeks 12 and 52. Conclusions Rimegepant showed favorable safety and tolerability in adults with migraine and a history of anxiety and/or depression and with SSRI and/or other antidepressant use. Trial Registration Clinicaltrials.gov: NCT03266588.